Intravenous amiodarone for the pharmacological termination of haemodynamically-tolerated sustained ventricular tachycardia: is bolus dose amiodarone an appropriate first-line treatment?. Issue 1 (21st December 2007) - Tomlinson, D R; Cherian, P; Betts, T R; Bashir, Y
Abstract : Objective: To examine the efficacy of bolus dose intravenous amiodarone for the pharmacological termination of haemodynamically-tolerated sustained monomorphic ventricular tachycardia (VT). Design, setting and participants: Retrospective case series of consecutive emergency admissions with haemodynamically-tolerated sustained monomorphic VT administered bolus dose intravenous amiodarone 300 mg, according to current UK advanced life support practice guidelines. Main outcome measures: Pharmacological termination rates within 20 min and 1 h and incidence of hypotension requiring emergency direct current cardioversion (DCCV) during this period. Results: 41 patients (35 men) of mean (SD) age 68 (10) years, the majority (85%) with ischaemic heart disease and impaired left ventricular function (mean (SD) ejection fraction 0.31 (0.11)), were enrolled in the study. The median VT duration was 70 min (range 15–6000), mean heart rate was 174 (34) bpm and systolic and diastolic blood pressures were 112 (22) and 73 (19) mm Hg, respectively. Pharmacological VT termination occurred within 20 min in 6/41 patients (15%; 95% CI 7% to 29%) and within 1 h in 12/41 patients (29%; 95% CI 18% to 45%). Haemodynamic deterioration requiring emergency DCCV occurred in 7/41 patients (17%; 95% CI 8% to 32%). Conclusions: Although advocated by advanced life support guidelines, bolus dose intravenous amiodarone was relatively ineffective for acutely terminating haemodynamically-tolerated sustained monomorphic VT with a significant incidence of haemodynamic destabilisation requiring emergency DCCV. Previous studies in the identical clinical setting suggest that alternative antiarrhythmic agents, particularly intravenous procainamide and sotalol, may be superior. A prospective randomised trial is required to determine the optimal drug treatment for stable sustained monomorphic VT in the emergency setting.